Factors Associated with Scaphoid Nonunion following Early Open Reduction and Internal Fixation - Prabhakar, Pooja; Wessel, Lauren; Nguyen, Joseph; Stepan, Jeffrey; Carlson, Michelle; Fufa, Duretti (Journal of Wrist Surgery, 2020)
Background Nonunion after open reduction and internal fixation (ORIF) of scaphoid fractures is reported in 5 to 30% of cases; however, predictors of nonunion are not clearly defined.Objective The purpose of this study is to determine fracture characteristics and surgical factors which may influence progression to nonunion after scaphoid fracture ORIF.Patients and Methods We performed a retrospective case–control study of scaphoid fractures treated by early ORIF between 2003 and 2017. Inclusion criteria were surgical fixation within 6 months from date of injury and postoperative CT with minimum clinical follow-up of 6 months to evaluate healing. Forty-eight patients were included in this study. Nonunion cases were matched by age, sex, and fracture location to patients who progressed to fracture union in the 1:2 ratio.Results This series of 48 patients matched 16 nonunion cases with 32 cases that progressed to union. Fracture location was proximal pole in 15% (7/48) and waist in 85% (41/48). Multivariate regression demonstrated that shorter length of time from injury to initial ORIF and smaller percent of proximal fracture fragment volume were significantly associated with scaphoid nonunion after ORIF (63 vs. 27 days and 34 vs. 40%, respectively). Receiver operating curve analysis revealed that fracture volume below 38% and time from injury to surgery greater than 31 days were associated with nonunion.Conclusion Increased likelihood for nonunion was found when the fracture was treated greater than 31 days from injury and when fracture volume was less than 38% of the entire scaphoid.Level of Evidence This is a Level III, therapeutic study.
Keywords: postoperative; scaphoid fracture; nonunion; open reduction internal fixation; open reduction and internal fixation